Avaliação microbiológica de circuitos respiratórios e anestésicos submetidos ao processo de desinfecção térmica - Oliveira, Andréa Ranucci (2012)
Introduction: The reprocessing and reuse of medical practices are common in health care institutions in Brazil and several countries. However, it is necessary to establish parameters to guide the development, validation and implementation of reprocessing protocols, in order to ensure product quality and safety and health of patients. This conduct is an important infection control action, because microorganisms can remain in reprocessed medical supplies and cause a wide variety of infectious processes. Objective: To evaluate the efficiency of thermal disinfection procedure adopted for the reprocessing of breathing circuit used in anesthesia and mechanical ventilation in two hospitals in São José do Rio Preto, SP. Method: We performed microbiological tests for the detection, identification, assessment of antimicrobial susceptibility of microorganisms from the respiratory and anesthetic circuits termodesinfetados in two hospitals. Results: The Hospital identified in two samples coagulase-negative Staphylococcus and Pseudomonas aeruginosa, samples of Enterococcus spp termodesinfectadora identified, water samples were found P. aeruginosa and Citrobacter freundii, yeasts and Gram-negative bacilli. In hospital B samples showed contamination with Gram positive samples subjected to drying and termosesinfecção were contaminated by Acinetobacter calcoaceticus. Samples collected from the inner surfaces of the dryer were isolated A. calcoaceticus, A. baumannii, and Achromobacter xylosoxidans. Conclusion: We note that the thermal disinfection process was not efficient for the elimination of pathogens in peer-reviewed articles and drying equipment can act as contaminants after the disinfection process.